2019
DOI: 10.1038/s41550-019-0765-4
|View full text |Cite
|
Sign up to set email alerts
|

The origin of radio emission from radio-quiet active galactic nuclei

Abstract: The central nuclei of galaxies, where super-massive black holes (SMBHs) are thought to reside, can experience phases of activity when they become Active Galactic Nuclei (AGN). An AGN can eject winds, jets, and produce radiation across the entire electromagnetic spectrum. The fraction of the bolometric emission in the radio spans a factor of ∼10 5 across the different AGN classes. The weakest radio sources, radio-quiet (RQ) AGN, are typically 1,000 times fainter than the radio-loud (RL) AGN, and represent the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
199
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(234 citation statements)
references
References 173 publications
14
199
0
Order By: Relevance
“…The latter is a combination of free-free emission, which has an almost flat radio spectrum, and steep synchrotron emission from supernova remnants. When combined, these lead to an observed spectral index of ∼0.7, which is characteristic of star-forming galaxies, and roughly in agreement with the spectral indexes of our sources (e.g., Condon 1992;Panessa et al 2019).…”
Section: Star Formation At Low Frequenciessupporting
confidence: 87%
“…The latter is a combination of free-free emission, which has an almost flat radio spectrum, and steep synchrotron emission from supernova remnants. When combined, these lead to an observed spectral index of ∼0.7, which is characteristic of star-forming galaxies, and roughly in agreement with the spectral indexes of our sources (e.g., Condon 1992;Panessa et al 2019).…”
Section: Star Formation At Low Frequenciessupporting
confidence: 87%
“…This suggests that the fundamental differences between rQSOs and cQSOs become apparent at R < −3.4, possibly due to a different process starting to dominate the radio emission. However, whether this process is due to AGN-driven winds, frustrated jets, star-formation or a coronal component (to name a few) is unclear (Zakamska & Greene 2014;Kellermann et al 2016;Laor et al 2019;Panessa et al 2019;Jarvis et al 2019). An enhanced fraction of broad absorption line QSOs (BALQ-SOs; known to host powerful winds) have been found in red QSOs (Urrutia et al 2009), which could be evidence that red QSOs are more wind dominated than typical QSOs.…”
Section: S82 14 Ghzmentioning
confidence: 99%
“…where νL ν is the radio power andf R is a dimensionless factor. In general, the radio emission of radio-quiet sources can have different origins (Panessa et al 2019, and references therein); in any case, assuming that the observed 1.4 GHz flux of HE 1143-1810 is due to a jet, and takingṁ = 0.8 and r J = 19 R G , we derivẽ f R = 1.3 × 10 −9 . Interestingly, this factor is not too far from that derived by Marcel et al (2019) for the X-ray binary GX 339-4 (f R = 4.5 × 10 −10 ).…”
Section: A Jet-emitting Disc?mentioning
confidence: 99%